The intersectional triad constructs and the future of social work in Africa: Social development, decolonisation and professional social work regulation - Engelbrecht, Lambert K.; Kurevakwesu, Wilberforce (Social Work/Maatskaplike Werk, 2025)
Social work in Africa remains a developing profession, still defining its identity and scope. Recent scholarship has emphasised the adoption of a social development approach, the integration of decolonial perspectives, and the establishment of professional regulation as key mechanisms for advancing the profession on the continent (cf. Chidyausiku & Bohwasi, 2021; Kurevakwesu, 2023). Although distinct, these three constructs intersect in ways that strengthen social work’s professional voice and enhance its capacity to respond to local and global challenges.